Prevalence of Ear, Nose & Throat diseases and Adequacy of ENT training among General Physicians - Farooq, Muhammad; Ghani, Shakeel; Hussain, Sadiq (International Journal of Pathology, 2018)
Background: Among general physiciens (GPs) consultations, Ear, Nose and Throat (ENT) diseases account for about 25% inadults and up to 50% in children. General physiciens are required to have adequate training to deliver efficient primary healthcare. This study was aimed to find prevalence of ENT diseases and adequacy of ENT training among GPs in Azad Jammu andKashmir (AJK).Methods: This prospective study was conducted among hundred (100) GPs; having more than 1 year experience, of majorcities of AJK. A performa was designed and distributed. The responses were collected and analysed.Results: Prevalence of ENT diseases in adults was 24% and in children 38%. Majority of GPs (72-96%) stated that thereshould be improvement in undergraduate training and arrangement of 4−8 weeks ENT house job rotation as well as ENTcontinuous medical education (CME) programs.Conclusion: There is some competency deficiency in GPs regarding ENT related primary health care; which can beminimized by improving under-graduate, house job and CME training.